Factors associated with clean and healthy living behavior among elementary school students - Evi Santri; Masryna Siagian; Hartono Hartono (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2026)
Background: Clean and Healthy Living Behavior (PHBS) in schools is a government program implemented through community health centers to improve public health status. Elementary school-aged children are a vulnerable group for various diseases associated with PHBS. This study aimed to identify factors associated with PHBS among students at public elementary schools in Banda Aceh City. Methods: A quantitative study with a cross-sectional design was conducted from November 2023 to January 2024. The population comprised 192 students, with a sample of 85 fourth and fifth grade students selected through purposive sampling. Data were collected using questionnaires and checklists and analyzed using the Chi-Square test. Results: Results showed that most respondents were male (51.8%) and aged 5-11 years (61.2%). More than half of respondents (56.5%) demonstrated poor PHBS, 65.9% had low knowledge levels, 45.9% reported unavailable PHBS facilities and infrastructure, and 60.0% perceived teacher roles as poor. Bivariate analysis revealed significant associations between knowledge level (p=0.024) and availability of facilities and infrastructure (p=0.004) with PHBS; however, no significant association was found between teacher role and PHBS (p=0.562). Conclusion: In conclusion, knowledge level and availability of facilities and infrastructure were significantly associated with PHBS among public elementary school students in Banda Aceh City. It is recommended that community health centers conduct regular PHBS education in schools and that schools complete necessary facilities while strengthening supervision of student PHBS implementation.